Assessment of the impact of agricultural support on crop diversity - Zdeňka Žáková Kroupová; Lukáš Čechura; Matěj Opatrný; Zuzana Hloušková; Iveta Mlezivová (Charles University in Prague, Institute of Economic Studies (IES), 2022)
Our results indicate that there is limited effect of agricultural subsidies on the agricultural biodiversity. By using unique farm-level data, we show that subsidies support rather income of farmers than agricultural biodiversity. The results are robust to size, practice management and altitude of operating of agricultural holdings and to various measures of agricultural biodiversity. However, when interpreting the results, the limitations of biodiversity indices should be considered.
Keywords: Q12; Q15; Q57; 330; biodiversity index; subsidies; panel data regression; Czech Republic